2017
DOI: 10.3389/fpls.2017.01659
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SlGRAS40 in Tomato Enhances Tolerance to Abiotic Stresses and Influences Auxin and Gibberellin Signaling

Abstract: Abiotic stresses are major environmental factors that inhibit plant growth and development impacting crop productivity. GRAS transcription factors play critical and diverse roles in plant development and abiotic stress. In this study, SlGRAS40, a member of the tomato (Solanum lycopersicum) GRAS family, was functionally characterized. In wild-type (WT) tomato, SlGRAS40 was upregulated by abiotic stress induced by treatment with D-mannitol, NaCl, or H2O2. Transgenic tomato plants overexpressing SlGRAS40 (SlGRAS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 55 publications
1
58
0
Order By: Relevance
“…To date, few reports have documented a role of GRAS proteins in drought stress. For example, NtGRAS1 in tobacco (Czikkel and Maxwell, 2007), BnLAS in B. napus (Yang et al, 2010), PeSCL7 in Poplar (Ma et al, 2010), OsGRAS23 in rice (Kai et al, 2015), and SlGRAS40 in tomato (Liu et al, 2017) were found to be involved in drought stress. In this study, the increased drought tolerance in BrLAS overexpressing plants provides novel evidence of the role of GRAS proteins in drought stress responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few reports have documented a role of GRAS proteins in drought stress. For example, NtGRAS1 in tobacco (Czikkel and Maxwell, 2007), BnLAS in B. napus (Yang et al, 2010), PeSCL7 in Poplar (Ma et al, 2010), OsGRAS23 in rice (Kai et al, 2015), and SlGRAS40 in tomato (Liu et al, 2017) were found to be involved in drought stress. In this study, the increased drought tolerance in BrLAS overexpressing plants provides novel evidence of the role of GRAS proteins in drought stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Rice OsGRAS23 is also involved in drought and oxidative stress tolerance via regulation of stress-related gene expression (Kai et al, 2015). Overexpression of the SlGRAS40 gene in tomato was also found to enhance tolerance to abiotic stress and influence auxin and gibberellin signaling (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Salt stress on transgenic lines was done according to the modified method described by Liu et al (2017) [2]. Each plant was planted in an independent basin (same basins were used), 11 or 10 plants of wild-type and CaSBP12 transgenic lines were placed in a big pot and watered once a week to make sure the soil water in every basin was uniform and all the plants were grown in the same conditions.…”
Section: Stress Treatments and Samples Collectionmentioning
confidence: 99%
“…Plants frequently encounter stressful environmental conditions, such as high salinity, extreme temperatures, drought, pests, and fungus infection [1]. These leading to detrimental effects on plant growth and seed germination and fruit productivity [2]. Salinity is the principal cause of crop yield loss worldwide and adversely affects plant growth and productivity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation